Strategies for self-management support by patients with stroke: integrative review - Huana Carolina Cândido Morais; Nathalia Costa Gonzaga; Priscila de Souza Aquino; Thelma Leite de Araujo (SciELO, 2015)
OBJECTIVE To analyze strategies for self-management support by patients with stroke in the light of the methodology of the five A's (ask, advice, assess, assist and arrange). METHODS Integrative review conducted at the following databases CINAHL, SCOPUS, PubMed, Cochrane and LILACS. RESULTS A total of 43 studies published between 2000 and 2013 comprised the study sample. All proposed actions in the five A's methodology and others were included. We highlight the Assist and Arrange, in which we added actions, especially with regard to the use of technological resources and joint monitoring between patients, families and professionals. No study included all five A's, which suggests that the actions of supported self-management are developed in a fragmented way. CONCLUSION The use of five A's strategy provides guidelines for better management of patients with stroke with lower cost and higher effectiveness.